Impact of biochar and hydrochar addition on water retention and water repellency of sandy soil - Abel, Stefan; Peters, Andre; Trinks, Steffen; Schonsky, Horst; Facklam, Michael; Wessolek, Gerd (Geoderma, 2013)
Application of biochar (BC) and hydrochar (HTC) in soils is being increasingly discussed as a means to sequestrate carbon and improve chemical and physical properties for plant growth. Especially the impact on physical properties is not well investigated so far. We study the impacts of biochar (BC) and hydrochar (HTC) on water retention characteristics (WRC) as well as on the wettability of sandy soils, using lab and field studies. Sandy soils with different amounts of organic matter were mixed with BCz (feedstock maize) and HTC (feedstock maize silage). Added amounts were 1, 2.5, and 5wt.%, respectively. The mixtures were packed in 100cm3 soil columns. In a field campaign identical amounts of BCf (feedstock beechwood) were added to the soil. Six months after incorporation undisturbed soil samples were taken. For these field samples available water capacity (AWC) was determined. For the packed soil columns the WRC was measured in the pressure head range from saturation to wilting point (−15,848cm). The extent of water repellency was determined for all samples using the water drop penetration time test. Addition of biochar leads to a decrease in bulk density, an increase in total pore volume as well as an increase in water content at the permanent wilting point. An increase in AWC could be observed for all sandy substrates used, except for the highly humic sand. Notable differences in the effects on the AWC could be measured among the three chars used. Particle size distribution of the chars as well as their consistency had different impacts on the pore size distribution of the soil matrix. No direct impact of the chars on the wettability of the soils could be observed. Local spots with hydrophobic character were detected among the samples with hydrochar, attributed to fungal colonisation. •We determined water retention and wettability of biochar and hydrochar amended soils.•Water retention data is described by unimodal and bimodal retention functions.•We observed an increase in available water capacity due to char amendment.•Water content at permanent wilting point is raised.•We did not observe direct impacts on wettability of soil by char admixture.